(untitled) (Journal of Dhaka National Medical College & Hospital, 2014)
Urinary tract infection is the most common infectious disease in the community medical practice. It was a cross-sectional descriptive study conducted on patients diagnosed with UTI. The objective was to study the prescribing pattern of antibiotic used in the treatment of UTI. The study was carried out in the OPD of Medicine, Surgery and Gynaecology & Obstetrics from 1st January to 31st March 2012 in Sir Salimullah Medical College and Mitford Hospital and Dhaka National Medical College Hospital, Dhaka. Urinary Tract Infection patients who were in the age group of 18-80 years were included after obtaining their informed consent. A suitable data collection form was prepared and used to collect the required data. Among 360 patients 180 from Sir Salimullah Medical College and 180 from Dhaka National Medical college. Most of the patients were prescribed with Ceftriaxone, Cefotaxime and ciprofloxacin respectively in Sir Salimullah Medical college and cefotaxime, nitrofurantoin and ciprofloxacin respectively in Dhaka National Medical College. The study found that Cephalosporin’s were most commonly used and Quinolones were the second most commonly used drugs for the treatment of UTI. The third category drug used in female patients was Nitrofurantoin which is relatively inexpensive and safe for both pregnant and non-pregnant women. J. Dhaka National Med. Coll. Hos. 2014;20(01):25-29